A survey of physical activity in dialysis patients in Northern Norway - An observational study - Vangen, Kjell-Gunnar (UiT Norges arktiske universitet, 2019)
Background: Patients in advanced stages of chronic kidney disease (CKD), especially patients treated with dialysis, have reduced physical capacity. The main objective of this project was to study and compare the degree of physical activity (PA) in patients in haemodialysis (HD) and peritoneal dialysis (PD) in Nordland, Troms and Finnmark. To our knowledge this is the first study to include accelerometer recordings of patients in both HD and PD. Methods: An observational study was conducted during 15. November to 15. December 2018. Patients were recruited in hospitals and dialysis satellites by mainly nephrologist and dialysis nurses. Each patient participated voluntarily and signed a written consent. The study consisted of a self-administered questionnaire about PA and health-related quality of life, and accelerometer recordings for seven days for objective measurements of PA. Results: Thirty patients out of 181 on chronic dialysis participated in the study, whereas 22 in HD and 8 in PD. Twenty-eight percent of all invited patients consented and were included in the study. Median wear time for ActiGraph accelerometer was significantly higher (P < 0,05) in the HD group with 9194,5 (8501-9733) minutes compared to PD 7509 (6400-9134) minutes. Seven out of 22 HD patients (31,8%) and five out of eight PD patients (62,5%) reached the recommended weekly goal of ≥ 150 minutes moderate-to-vigorous physical activity (MVPA). Only one patient had an active lifestyle in terms of average steps daily (≥ 7500), three patients classified to somewhat active (5000-7499 steps/day), whereas 26 were categorised as sedentary. Haemoglobin was significantly associated with daily MVPA at or above vs. below median (OR 0,39 (95% CI 0,15-0,99) per 1 g/dL increase; P = 0,047). Most patients reported that they had never been informed by their nephrologist about the potential benefit of being physically active, but a desire to be more active was commonly found. Conclusion: Results from this study indicate that dialysis patients have a low ...